Induction of tolerance by monoclonal antibody therapy. - Benjamin, R; Waldmann, H (1986)
A major goal in immunology has been to find a means of selectively abolishing an individual's potential to mount an immune response to certain antigens, while preserving responsiveness to others. The facility to induce such specific immunological unresponsiveness in an adult would have major implications for tissue-grafting, the control of allergy and for treatment of autoimmune disease. Classical work has shown that immunosuppressive regimes, such as irradiation, anti-lymphocyte globulin or thoracic duct drainage, may facilitate tolerance induction. We describe here a technique by which the immune system of mice can be manipulated to be tolerant to certain protein antigens by administering these during a brief pulse of treatment with a monoclonal antibody directed to the L3T4 molecule on helper T lymphocytes. This technique has the potential to form the basis of a novel generalized means of tolerance induction.